Likuiditas, Leverege, Profitabilitas dan Pengaruhnya terhadap Nilai Perusahaan Sub Sektor Transportasi di Indonesia - Nurhanif, Muhammad Azka; Malinda, Shelfi; Yuliani, Yuliani (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aims to analyze the effect of liquidity, leverage, and profitability on firm value. This study uses a quantitative method. The data used in this study is secondary data with data collection technique through Indonesia Stock Exchange and IDN Financial. The population used in this study are all transportation sub-sector companies listed on the Indonesia Stock Exchange in 2016-2021. This study used a purposive sampling method to select the number of samples that obtained 8 companies. The data analysis technique used is multiple linear regression analysis. The results showed that simultaneously liquidity, leverage, and profitability affect firm value. Partially, liquidity and leverage have a positive effect on firm value, while profitability has no effect on firm value. Keywords : Liquidity, Leverage, Profitability, Firm Value